Environmental Technologies to Treat Sulphur Pollution: Principles and Engineering 2020
DOI: 10.2166/9781789060966_0247
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical removal of sulfur pollution

Abstract: Sulfur compounds are common contaminants in gaseous and aqueous waste streams such as sour gases, sewage and industrial wastewaters. The broad range of sulfur compounds contained in the wastewater, as well as the total sulfur concentration, the pH range and the presence of additional contaminants, e.g. organic compounds or trace metals, will define the selection of the treatment strategies. Sulfur pollution treatment today comprises a wide range of biological (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
(133 reference statements)
0
4
0
Order By: Relevance
“…This can be an advantage over the chemical-intensive processes to use chemical-less electrical oxidation instead of dosing, transport, and storage of potentially toxic material to conduct an oxidation process [377]. Furthermore, easy control of the cell performance by adjustable operational parameters, such as current and voltage, and no limit on electron flux are significant advantages over some technologies like photocatalytic reactors [378]. The energy expense of an electrochemical cell sometimes is the most dominant problem in field applications.…”
Section: Electrochemical Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be an advantage over the chemical-intensive processes to use chemical-less electrical oxidation instead of dosing, transport, and storage of potentially toxic material to conduct an oxidation process [377]. Furthermore, easy control of the cell performance by adjustable operational parameters, such as current and voltage, and no limit on electron flux are significant advantages over some technologies like photocatalytic reactors [378]. The energy expense of an electrochemical cell sometimes is the most dominant problem in field applications.…”
Section: Electrochemical Processesmentioning
confidence: 99%
“…IEM selectively transfers positively or negatively charged ions. Reprinted from [378]. Licensed under CC BY-NC-ND 4.0. reactions.…”
Section: Electrochemical Processesmentioning
confidence: 99%
“…A bioelectrochemical system (BES) employs microorganisms and electrodes to catalyze redox reactions and this system can be utilized in a two-chamber microbial fuel cell using either the anode, cathode or both as bioelectrodes (Ntagia et al, 2020;Sánchez et al, 2020). Electroactive microorganisms can extract electrons that can be utilized to generate electricity, treat wastewater by redox reactions and also recover nutrients (i.e., P, N), sulfur (Ntagia et al, 2020) and metals (Nancharaiah et al, 2016a). Removal of individual selenate (Sravan et al, 2020), selenite (Catal et al, 2009), NO 3 − (Nancharaiah et al, 2016b) and SO 4 2− (Luo et al, 2017) using BESs has been reported in the literature.…”
Section: Bioelectrochemical Processesmentioning
confidence: 99%
“…Among various alternative methods, involving thermal decomposition, photochemical, , and plasma technologies, , electrolysis of H 2 S provides a cleaner and cost-effective approach. The direct electrolysis of H 2 S proceeds with the following half-reactions: SOR (eq ) at the anode (0.14 V) and HER (eq ) at the cathode (0.00 V), enabling the overall H 2 S splitting to take place at −0.14 V vs NHE . This results in less energy consumption than simple H 2 O electrolysis, and besides H 2 (green fuel), the value-added sulfur produced after electrolysis can be used as a cathode material in sulfur-based batteries resulting in a circular economy. , Therefore, replacing OER with SOR provides relatively favorable and energy-saving H 2 production. anode : n HS + OH normalS n 2 + n normalH 2 normalO , 0.25em 1 n 4 cathode : 2 normalH + + 2 normale normalH 2 …”
Section: Introductionmentioning
confidence: 99%